2017
DOI: 10.1016/j.ijscr.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Aplasia cutis congenita as a result of interstitial laser therapy for fetal reduction in monochorionic twins: Conservative approach and outcome

Abstract: HighlightsLaser therapy for fetal reduction could be associate with Aplasia Cutis Congenita.Despite of size of lesion conservative treatment could be an effective option.Extreme prematurity did not affected degree of spontaneous epithelization.Patient was followed up to 5 years and no complications were detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
4
1
Order By: Relevance
“…This differs from published experience that death before 14 weeks of gestation results in ACC usually on the trunk, while after 14 weeks it is mostly on the extremities 7 . The same pattern of symmetrical, extensive ACC occurs after selective foetal reduction, and in both situations can be attributed to placental damage secondary to twin death, without implicating laser burns 8 …”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…This differs from published experience that death before 14 weeks of gestation results in ACC usually on the trunk, while after 14 weeks it is mostly on the extremities 7 . The same pattern of symmetrical, extensive ACC occurs after selective foetal reduction, and in both situations can be attributed to placental damage secondary to twin death, without implicating laser burns 8 …”
Section: Resultscontrasting
confidence: 77%
“…7 The same pattern of symmetrical, extensive ACC occurs after selective foetal reduction, and in both situations can be attributed to placental damage secondary to twin death, without implicating laser burns. 8 Type 6: aplasia cutis congenita associated with epidermolysis bullosa (Bart syndrome)…”
Section: Type 1: Scalp Aplasia Cutis Congenita Without Multiple Anomaliesmentioning
confidence: 99%
“…One case series reported ACC incidence of 8% (2 of 26 newborns after laser ablation at 13 and 14 weeks) after MFPR. 10 One similar case report suggested that the mechanism of ACC was laser burn 11 ; however, a baby born after spontaneous cotwin loss during a MCDA pregnancy presented similar truncal and thigh lesions characteristic of ACC type 5, 12 thereby disproving laser burn as the plausible cause.…”
Section: The Incidence Of Multiple Gestation In Southmentioning
confidence: 99%
“…The exact etiology of ACC is not completely understood. Several factors have been proposed as possible causes, e.g., vascular disruption, thrombotic events, trauma, amniotic defects, chromosomal abnormalities or gene mutations, ectodermal dysplasia, defective closure of the neural tube, and teratogenic events such as intrauterine infections, or drugs and medications during pregnancy [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The most common lesion location of ACC is the scalp in 70% [ 7 , 8 ]; however, any skin site can be affected [ 7 ]. The estimated incidence of ACC is approximately 0.5–3 in 10,000 newborns [ 2 , 5 ], regardless of gender or ethnicity [ 5 ]. The clinical appearance of ACC is heterogeneous and it can be associated with various systemic congenital anomalies.…”
Section: Introductionmentioning
confidence: 99%